Clustering-Triggered Emission of Carboxymethylated Nanocellulose - Li, Meng; Li, Xiaoning; An, Xuefei; Chen, Zhijun; Xiao, Huining (Frontiers in Chemistry, 2019)
Non-conjugated polymers with luminescence emission property have recently drawn great attention due to their promising applications in different areas. Most traditional organic synthetic non-conjugated polymers required complicated synthesis (Chen et al., 2018a). Herein, we report a nonconjugated biomass material, carboxymethylated nanocellulose (C-CNC), which is found to be practically nonluminescent in dilute solutions, while being highly emissive when aggregated as nanosuspensions. We propose that the luminescence of C-CNC originates from the through-space conjugation of oxygen atoms and carboxyl groups of C-CNC. Thus, a clearer mechanism of clusteroluminescence was provided with the the subsequent experiments. The effects of concentration of C-CNC, solvent, temperature and pH have also been investigated. In addition, ethylenediamine (EDA) has been employed to “lock” C-CNC material via the bonding of amide group with carboxylic groups. As prepared C-CNC/EDA confirmed that the clusteroluminescence was attribute to the amide moieties and through-space conjugation between oxygen and carbonyl moieties. Density functional theory (DFT) calculations have also been employed to confirm the luminescence mechanism. It is believed that such clustering-triggered emission mechanism is instructive for further development of unconventional luminogens.